2022
DOI: 10.1088/1361-6439/ac7bcf
|View full text |Cite
|
Sign up to set email alerts
|

A microfabricated semi-packed column coated with porous layer and ionic liquid for the separation of characteristic markers of non-alcoholic fatty liver disease

Abstract: A serpentine-shaped semi-packed micro gas chromatography (GC) column with mesoporous inner surface and ionic liquid (IL) coating was developed for the separation of various typical volatile organic compounds (VOCs) in exhaled air. The mesoporous surface was prepared by coating silica nanoparticles on the inner surface of the micro GC column through static method and used as stationary phase support to improve the separation performance by its high surface area. The micro GC columns provide efficient separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Although the tiny size of the on-chip micro GC-column unit dictates that its column length is much shorter than that of traditional capillary columns, our previous work showed that modification of mesoporous silica microspheres and the proper stationary phase can achieve better separation performance than traditional capillary chromatographic columns [21]. The rough mesoporous silica microspheres with particle sizes ranging from 140 to 180 nm and uniform distribution to achieve approximately 2.5 nm pores are effective support materials for stationary phases.…”
Section: On-chip Micro Gc-column Unitmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the tiny size of the on-chip micro GC-column unit dictates that its column length is much shorter than that of traditional capillary columns, our previous work showed that modification of mesoporous silica microspheres and the proper stationary phase can achieve better separation performance than traditional capillary chromatographic columns [21]. The rough mesoporous silica microspheres with particle sizes ranging from 140 to 180 nm and uniform distribution to achieve approximately 2.5 nm pores are effective support materials for stationary phases.…”
Section: On-chip Micro Gc-column Unitmentioning
confidence: 99%
“…Traditional stationary phases with poor oxygen tolerance [24] (such as polydimethylsiloxane) undergo degradation and column bleeding in oxygen environments, exhibiting drifting baselines and chromatographic peak tailing phenomena in chromatograms. Previous studies have shown the effectiveness of ionic liquids (ILs) in separating non-alcoholic fatty liver disease characteristic markers [21]. Therefore, in this study, ultrasonically treated dichloromethane solution of trihexyl (tetradecyl) phosphonium bis (trifluoromethylsulfonyl) amide was statically coated on the rough inner surface of the chromatographic column to form an IL film as the stationary phase.…”
Section: On-chip Micro Gc-column Unitmentioning
confidence: 99%
“…Generally, gas chromatography-mass spectrometry (GC-MS) is used to detect trace isoprene gas due to its high accuracy and good specificity, while the high cost and bulky equipment prevent it from being use in the pointof-care-testing (POCT). Some studies developed the miniaturized components of GC systems, such as GC columns and gas sensors by micro electro mechanical systems (MEMS) technology and applied them in the portable breath detection [5][6][7][8]. However, despite of progress in the detection ability of the micro GC, at present, the detection limits of the micro GC systems were still at the order of ppm and they hardly met the accurately quantitative analysis of breath VOCs at low concentrations [9,10].…”
Section: Introductionmentioning
confidence: 99%